Sleep Patterns and Health Behaviors in Healthcare Students. - Nugent, Kenneth; Raj, Rishi; Nugent, Rebecca (Southern Medical Journal, 2020)
Objectives: Personal health behavior can influence the academic development of healthcare students. This study was designed to evaluate the personal health behavior, including sleep time, of healthcare students at a large health sciences center.Methods: An anonymous online survey based on standardized questionnaires about sleep, insomnia, depression, alcohol use, and exercise was sent to all of the healthcare students (including medical, nursing, pharmacy, graduate biomedical science, and allied health students) in the Texas Tech University Health Sciences Center graduate education programs in Lubbock.Results: In total, 412 students replied to this survey. Their mean sleep duration during the weekday was 7.5 ± 1.2 hours; 16.5% were short sleepers (<7 hours) during weekdays; 33% of the students woke up "feeling tired or worn out" >15 days during the last month. Many students were either moderately or severely bothered by "the lack of energy" because of poor sleep, and 56.6% of students rated their sleep as either fair or poor. Approximately 35% of students had drinking patterns that qualified as hazardous drinking, 6.3% of students smoked, and 23% of students did not do even mild exercise during the week. Eighty-nine percent of students reported stress in their life, including family stress, job stress, financial stress, legal stress, and other stress. Thirty-five percent of students considered their health as either poor or fair. Approximately 50% of students did not expect any change in their situation during the next 3 to 6 months.Conclusions: Although most healthcare students report adequate sleep times, more than half of them rate their sleep as fair or poor. In addition, some have poor health habits, including excessive alcohol use. Health science centers should introduce programs to promote healthy behaviors and reduce stress in healthcare students.